Pediatric Uveitis: Experience in Colombia (2016)
Purpose: To describe the clinical features of uveitis in children treated at two ophthalmologic centers in Bogotá, Colombia, in a 13 year-period. Methods: Retrospective observational clinical record review of pediatric children with diagnosis of uveitis. Results: In total, 310 children were evaluated, 51.9% were female, mean age of 10.1 years. Posterior uveitis was the most common location (58.7%), of insidious onset (87.4%) and chronic course (78.1%). The most common etiology was infection (58.4%) caused by toxoplasmosis (76.8%). There was a statistically significant difference in visual acuity between anterior (20/68) and intermediate uveitis (20/70), compared with posterior uveitis (20/434) (p less than 0.05). Conclusions: This is the first study to report the clinical features of pediatric uveitis in Colombia, where infectious etiologies are the leading cause. It will improve awareness and knowledge of pediatric uveitis in developing countries, and contribute to the development of public health policies of pediatric visual health. Received 12 September 2015; revised 23 February 2016; accepted 25 February 2016; published online 18 May 2016 © Taylor and Francis Group, LLC.